Association between stigma, psychological distress, and quality of life among people living with HIV in federal territory of Kuala Lumpur / Khairiah Ibrahim - Khairiah, Ibrahim (2020)
Quality of life is an important component in the evaluation of the well-being of PLHIV. However, HIV stigma and psychological distress (depression, anxiety and stress) continue to be a barrier to obtain a good quality of life among PLHIV globally. This study assesses the level of QOL, stigma and psychological distress among PLHIV in Kuala Lumpur by determining the association between QOL, stigma and psychological distress. A cross-sectional study was conducted, involving 305 PLHIV attendees of the infectious disease clinic in a teaching hospital, primary health clinic and three Community-Based Organisations (CBOs). The sampled respondents completed face to face interviews using a standardised structured questionnaire on quality of life scale (WHO-QOL HIV BREF), Depression, Anxiety and Stress Scale (DASS) and HIV Stigma Scale. Total quality of life of respondents in this study was in the low to moderate range (mean 93.7; SD 15.6) and was significantly impaired by the social relationship domain (mean score 12.9; SD 3.2) followed by the spirituality domain (mean score 12.4; SD 2.4). On the other hand, psychological domain (mean score 13.8; SD 2.7) and ability to perform daily activities (physical domain) was not affected by the illness (mean score 13.7; SD 3.08). The mean total QOL was significantly higher among respondents from the teaching hospital and primary health clinic compared to CBOs respondents, which could be due to the availability of HAART treatment. The overall stigma experienced by PLHIV in this study was moderate (mean score 100.4; SD 17.3). Stigma was highest in the disclosure domain, where difficulty to disclose HIV serostatus may be influenced by the cultural and religious iv belief of PLHIV. It is interesting to note that PLHIV in this study least experienced negative self-image stigma (shame and guilt). This may reflect them having a high perceived stigma but low internalised stigma, which suggests they did not experience the negative consequences of stigma. Stigma was associated with higher odds of depression (Adjusted OR 1.05, 95% CI 1.02-1.07), anxiety (Adjusted OR 1.04, 95% CI 1.02-1.06) and stress (Adjusted OR 1.03, 95% CI 1.00-1.06) and was negatively correlated with all QOL domains. This study also found that psychological manifestation was prevalent among PLHIV with 48.7% of respondents having depression, 58.4% anxiety and 30.5% stress. Depression, anxiety and stress were negatively associated with all QOL domains and associated with lower odds of good quality of life (Adjusted OR 0.92, 95% CI 0.89- 0.94) for depression, (Adjusted OR 0.94, 95% CI 0.92-0.96) for anxiety and (Adjusted OR 0.92, 95% CI 0.90-0.95) for stress. In conclusion, these findings confirm that stigma and psychological distress make a distinctive, significant contribution to overall QOL. Therefore, focus on efforts to diagnose and treat depression, anxiety and stress while enhancing spiritual and psychological support are strategies to improve QOL among PLHIV. Finally, it is important to address disclosure stigma among PLHIV by having active interaction between PLHIV with healthcare workers, family members, employers and the society to empower and provide safe disclosure among PLHIV. Keywords: PLHIV, QOL, depression, anxiety, stress, stigma, HAART